Analisis Determinan Neraca Perdagangan Daging Sapi di Indonesia Periode 2013-2023 - Reza Agung Amijaya; Syarif Imam Hidayat; Nuriah Yulianti (Program Studi Peternakan Universitas Muslim Maros, 2026)
The Indonesian beef trade balance consistently faces a deficit, a structural issue driven by the imbalance between high demand and low domestic production. This study analyzes the factors that determine Indonesia's beef trade deficit from 2013 to 2023. The gap between high consumption growth and limited domestic production capacity has created a chronic dependence on imports, a structural problem that requires focused policy intervention. This research uses a quantitative approach with a multiple linear regression model. It examines the influence of beef production, beef consumption, the rupiah exchange rate against the US dollar, and trade policies on the trade balance. Secondary data were analyzed using classical assumption tests, F-tests, t-tests, and the coefficient of determination. The analysis shows that only the beef production variable has a significant and negative impact on the trade balance. Statistically, every 1,000-ton increase in domestic production can improve the trade deficit by 4.811 thousand US dollars. Meanwhile, the variables for consumption, exchange rates, and trade policies were not found to have a statistically significant effect, although the direction of their relationship aligns with economic theory. These findings highlight that the most effective strategy to overcome the beef trade deficit is to strengthen the fundamentals of the domestic production sector.